-2(3y-4)-y=-4(y-2)

Simple and best practice solution for -2(3y-4)-y=-4(y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3y-4)-y=-4(y-2) equation:


Simplifying
-2(3y + -4) + -1y = -4(y + -2)

Reorder the terms:
-2(-4 + 3y) + -1y = -4(y + -2)
(-4 * -2 + 3y * -2) + -1y = -4(y + -2)
(8 + -6y) + -1y = -4(y + -2)

Combine like terms: -6y + -1y = -7y
8 + -7y = -4(y + -2)

Reorder the terms:
8 + -7y = -4(-2 + y)
8 + -7y = (-2 * -4 + y * -4)
8 + -7y = (8 + -4y)

Add '-8' to each side of the equation.
8 + -8 + -7y = 8 + -8 + -4y

Combine like terms: 8 + -8 = 0
0 + -7y = 8 + -8 + -4y
-7y = 8 + -8 + -4y

Combine like terms: 8 + -8 = 0
-7y = 0 + -4y
-7y = -4y

Solving
-7y = -4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4y' to each side of the equation.
-7y + 4y = -4y + 4y

Combine like terms: -7y + 4y = -3y
-3y = -4y + 4y

Combine like terms: -4y + 4y = 0
-3y = 0

Divide each side by '-3'.
y = 0

Simplifying
y = 0

See similar equations:

| 3(3x+2)=6(2x-3) | | 9x+3=7x-19 | | 2+15+15v=62 | | 40r^2-35r+16r-14=0 | | 50m+42750=42675-175m | | 4(2x-7)=3(x-1) | | 5y+35=x+5 | | G(10)=50 | | 7x-47=x | | G(7)=98 | | 8x+23=3x+128 | | 20(-2+x)+10=50(-1+4x) | | 8x-10=7x-5 | | F(4)=96 | | V^2+(6.6V)-51.48=0 | | a-152= | | y+.5= | | 10(-2+x)+10=50(-1+4x) | | 8w+4=24 | | 5x+4=5+2x+24 | | x^2+19x+32=0 | | x^2-(4+p)x+12=0 | | 3n+5/7= | | 9x^2-8x-71=0 | | 3x-8x+3=x-8+11 | | 3(x-5)=2(x+10) | | 9k+4+7d= | | 0.05+0.10(100-x)=0.45x | | 49+-10= | | 5w-4=3w+2 | | 6x-6=6+2x | | -6(7x+9)=8(9x-4) |

Equations solver categories